Problematika Penanganan Politik Uang pada Pemilihan oleh Sentra GAKKUMDU Kabupaten Kendal - Lidwina Yosieva; Riska Andi Fitriono (PLEDOI (Jurnal Hukum dan Keadilan), 2024)
Indonesia has a democratic form of government where the government system is from the people, by the people, and for the people (Kristina, 2021). Democracy as a means of people's sovereignty is realized by holding Legislative Elections and Regional Head Elections. Of course, the implementation of elections or regional elections cannot be separated from the violations that occur. These violations are divided into administrative violations, violations of the code of ethics, and violations of electoral crimes. The handling of each violation varies. Administrative violations are forwarded to the KPU, violations of the code of conduct are forwarded to the DKPP, and violations of electoral crimes are forwarded to the Sentra Gakkumdu (Integrated Law Enforcement Center). A concrete example of the violation of electoral crime is money politics regulated in Article 187A of the Regional Head Election Law. The purpose of this paper is to find out the problems in handling money politics in the Regional Head Election by the Sentra Gakkumdu Kabupaten Kendal so as to minimize the occurrence of money political practices in the Regional Head Election and the implementation of handling election violations in accordance with the rules so that the holding of elections is carried out in accordance with applicable regulations. This research is an empirical or non-doctrinal legal research with a qualitative approach. The techniques used in collecting legal materials in this study are observation, interviews, and documentation. The results of the study show that there are still several problems or obstacles faced by Sentra Gakkumdu, including community factors, law enforcement officials, and statutory factors..